Baby, unplugged : one mother's search for balance, reason, and sanity in the digital age - Brickman, Sophie (HarperOne, an imprint of HarperCollinsPublishers, 2021)
"Combining a journalist's investigative eye with her unborn second child as an experimental guinea pig, Baby, Unplugged draws on Sophie Brickman's own experiences as a journalist and parent to try to discover what aspects of technology are actually helpful, which are making us crazy, and most importantly, how we might learn to trust ourselves and our instincts again when it comes to raising children"--